The Concept of Qiwamah and Its Implications for Gender Justice in Islamic Family Law in Indonesia - Siti Aisyah; Ahdiyatul Hidayah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
Family is the most important element in the formation of a society. Islam has a very fair concept in family leadership. In Islam, rights and duties are always regulated in balance. This balance results in the establishment of a harmonious relationship between husband and wife in the family. This paper uses an analytical descriptive method that examines Qiwamah issues related to women's leadership in the household. And the aim of this research is to find out how the concept of Qiwamah and gender justice in Islamic family law against the concept of Qiwamah in its implications for gender justice. This paper uses analytical descriptive method. The results of this study found that Islam gives leadership in the family to husband and wife, if both have the qualifications to be leaders. Leadership is not only given to men (husbands) only. Leadership is given to both parties if both have leadership qualifications, be it wives or husbands. In Islam, leadership/ Qiwamah in the family aims to create harmonious conditions so that the family can achieve happiness both in this world and in the Hereafter.